Normative reference values of handgrip strength for Brazilian older people aged 65 to 90 years: Evidence from the multicenter Fibra‑BR study - Reichenheim, Michael Eduardo; Lourenço, Roberto Alves; Nascimento, Janaína Santos; Moreira, Virgílio Garcia; Neri, Anita Liberalesso; Ribeiro, Rodrigo Martins; Lustosa, Lygia Paccini; Ferriolli, Eduardo (PloS one, 2021)
Handgrip strength (HGS) is an indicator of muscle strength, suited for evaluating the aging process. Its use depends on the availability of reliable normative reference values (NRV). The main objective of this study is to provide NRV of HGS for Brazilians aged 65 to 90 years. Participants were from the Frailty in Brazilian Older People research. 2,999 successful aging (SA) participants comprised the development sample. HGS was measured using a hydraulic dynamometer. Obtaining NRV involved regressing HGS on age per sex-height strata, fitting separate fractional polynomial (FP) models for the mean and coefficient of variation. Model fit was assessed via standardized residuals, probability/quantile plots, and comparing observed to normal expected percentages of participants falling within specified centile intervals. For validation, the latter procedure was applied to 2,369 unsuccessfully aging (UA) participants. Across strata, the best-fitting models for the means were FP of power 1. FP models for the CV indicated age invariance, entailing steady heteroscedastic age decline in SD since coefficients for the means were negative and SD = CV×mean. All models adjusted well. Centiles distributions for the SA and UA populations showed anticipated patterns, respectively falling on and below the normative expected centile references. Results (NRV) are presented in tables and centile charts. Equations are also provided. NRV/charts may be endorsed for routine use, while still tested further. They would aid professionals caring for older people, not only to identify those at risk and eligible for immediate provisions, but also in planning prevention and rehabilitation measures.